Intravenous Glycoprotein IIb/IIIa Inhibitor (Tirofiban) followed by Intra-Arterial Urokinase and Mechanical Thrombolysis in Stroke - Mangiafico, Salvatore (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: The purpose of this study was to evaluate preliminarily the efficacy and safety of intravenous tirofiban combined with intra-arterial pharmacologic and mechanical thrombolysis in patients with stroke. METHODS: Twenty-one consecutive patients with an acute ischemic stroke due to major cerebral arteries occlusion and a National Institutes of Health Stroke Scale [NIHSS] score ≥18 were treated with an intravenous bolus of tirofiban and heparin followed by intra-arterial administration of urokinase coupled with mechanical thrombolysis. RESULTS: Thirteen patients had an anterior circulation stroke (T-siphon internal carotid artery [ICA]=7; middle cerebral artery [MCA]=6), 6 patients a posterior circulation stroke, and 2 patients an anterior plus posterior circulation stroke (left ICA or M1 tract of MCA plus basilar artery occlusions). Mean NIHSS score on admission was 21 (range, 18–27). Immediate recanalization was successful (thrombolysis in myocardial infarction [TIMI] 2–3) in 17 of 21 patients. The following day, 14 of 19 patients improved substantially and complete vessel patency (TIMI 3–4) was confirmed by digital subtraction angiography. Intracranial bleeding occurred in 5 of 21 patients (3 symptomatic cerebral hemorrhages and 2 subarachnoid hemorrhages) and was fatal in the case of 3 patients. At discharge, the mean NIHSS was 5.4 (range, 0–25). Overall, at 3-month follow-up the functional outcome was favorable (modified Rankin Scale score = 0–2) in 13 of 21 (62%) patients. Death (including all causes) at 90 days occurred in 6 of 21 (28%) cases. CONCLUSIONS: The combination of intravenous tirofiban with intra-arterial urokinase and mechanical thrombolysis may be successful in reestablishing vessel patency and result in a good functional outcome in patients with major cerebral arteries occlusions.